Description of Zoonostic Epidemiological Investigations In Dengue Hemorrhagic Fever (DHF) At Community Health Center of Lamaru - Nur Salsabillah; Ainur Rachman; Mardiana Mardiana; Erika Fitri; Resandriya Rida Robi'ah; Selvia Indriani (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the bite of the Aedes aegypti mosquito. This disease is still a health problem in Indonesia because the seasons are constantly changing and unpredictable, causing the disease to continue to rise and tends to be difficult to minimize. The main cause of this disease is related to the environment and the fact that there are still many mosquito larvae because the community does not carry out PSN (Mosquito Nest Eradication) and 3M Plus measures. And if the vector that causes DHF is not eradicated it can cause an outbreak. Epidemiological investigation activities are a form of community empowerment which aims to examine mosquito larvae which are vectors for DHF disease transmission and increase awareness of community behavior in carrying out DHF control and prevention. The method used was observation by observing the presence of Aedes aegypti mosquito larvae and interviews at RT 16, Lamaru Village, targeting DHF case sufferers and the people who live around it, as well as socialization regarding PSN DHF and 3M Plus and distribution of abate powder door to door. The results of the activities of the 20 houses examined were 75% positive for mosquito larvae in the bathtub and unused items in residents' homes with a larva-free rate of 25% where these results were still very low and did not meet the target of 95%. Efforts to prevent DHF can be increased through this activity with the community doing 3M Plus & PSN routinely every week.